2017
DOI: 10.1080/17451000.2017.1280170
|View full text |Cite
|
Sign up to set email alerts
|

Environment and life cycles influence distribution patterns of hydromedusae in austral South America

Abstract: We analysed hydromedusa assemblages of South America (from 22°S to 56°S and from 040°W to 080°W), their association with water masses and the influence of the life cycle on medusa distributions. The geographic distribution of 130 species of hydromedusae was compiled from literature reports (62 publications between 1913 and 2012). Seven areas were defined: Atlantic Magellanic, Argentinean, Pacific intermediate zone, Pacific Magellanic, Peruvian-Chilean, South Brazilian and Oceanic. The variance of the species-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
4
4
1
Order By: Relevance
“…The location of the G 8 group, which broadly followed the slope and was entirely composed by R . velatum , matched with previous biogeographic studies [14, 75] and with the oceanic feature that this holoplanktonic hydromedusa is associated with [77,78]. The austral assemblages, G 9 and G 10 groups, located mainly in the Magellanic Province and on the slope, correspond to hydromedusan species associated to sub-Antarctic waters [78,79].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The location of the G 8 group, which broadly followed the slope and was entirely composed by R . velatum , matched with previous biogeographic studies [14, 75] and with the oceanic feature that this holoplanktonic hydromedusa is associated with [77,78]. The austral assemblages, G 9 and G 10 groups, located mainly in the Magellanic Province and on the slope, correspond to hydromedusan species associated to sub-Antarctic waters [78,79].…”
Section: Discussionsupporting
confidence: 87%
“…The regional patterns observed in our study were in accordance to the biogeographic distribution of hydromedusan species in the region (see [14,75]). As stated by Rodriguez et al [75], the distributional patterns of hydromedusae in the temperature SWA were related to neritic water masses coinciding with previously suggested biogeographical provinces (i.e., the South Brazilian, the Argentine, and the Magellanic Provinces) ([27], see Fig 1).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…On the other hand, greater dispersal could help individuals get away from conspecifics to avoid competition in an environment with scarce resources (Comita, 2017) and/or decrease chances of predation and parasitism. In fact, species that release medusae usually have wider geographical ranges than benthic species (Gibbons, Buecher, Thibault-Botha, & Helm, 2010;Gibbons, Janson, Ismail, & Samaai, 2010;Rodriguez et al, 2017), although the opposite was found in the family Hydractiniidae (Miglietta & Cunningham, 2012 (Carré & Carré, 2000). It is important to note, however, that patterns inferred in this study are for depths below 50 m deep.…”
Section: Discussioncontrasting
confidence: 53%
“…On the other hand, greater dispersal could help individuals get away from conspecifics to avoid competition in an environment with scarce resources (Comita, ) and/or decrease chances of predation and parasitism. In fact, species that release medusae usually have wider geographical ranges than benthic species (Gibbons, Buecher, Thibault‐Botha, & Helm, ; Gibbons, Janson, Ismail, & Samaai, ; Rodriguez et al, ), although the opposite was found in the family Hydractiniidae (Miglietta & Cunningham, ). A reasonable explanation for the increased proportion of meroplanktonic records would be that the medusae released in deep‐sea environments are monoecious, an advantageous condition in an environment with scarce food, allowing for greater dispersal and colonization of new environments along with ease of sexual reproduction in an environment with low population densities.…”
Section: Discussionmentioning
confidence: 99%